Melatih Keterampilan Berpikir Kreatif melalui Pembelajaran Berbasis Proyek dalam Mempersiapkan Tenaga Kerja untuk Menghadapi Kompetisi Global - Muhammad Munib (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
Often we find the fact that skills gaps begin with the basic idea that many jobs exist, but skilled workers do not. The relationship exists between labor readiness, business and industrial development, and educational institutions have been around for a long time. However, this relationship cannot refute the fact that prospective employees are not ready to enter the workplace in the future. The Law of the Republic of Indonesia concerning the national education system addresses the importance of training in creative thinking skills by stating that the education system must develop the potential of students to be religious, respectful, well-educated, and competent in thinking creatively, independently, democratically, and responsibly. While empirical studies show that Indonesian students have unsatisfactory creative thinking skills. This study aims to describe how to train Creative Thinking Skills through project-based learning in preparing the Workforce to face global competition. From the results of the discussion it was concluded: 1) The government needs to be more serious in entering tertiary education and setting targets for maximum workforce readiness. 2) Educational institutions in their learning activities need to improve their mastery of high-level thinking skills in determining their educational success by improving high-level cognitive functions (metacognition, metamemory and metacomprehension, or assessing the truth of one's own memories; solving problems, or taking appropriate steps when dealing with unknown things, and think critically, or evaluate the quality of ideas). 3) For most educators today who are well connected and driven by technology, the mastery of technology literacy in education is still lacking, therefore mastery of technology literacy needs to be improved at the level of the teachers in this country. 4) Potential to integrate Project Based Learning (PBL) in the classroom to improve students' soft skills which in turn will ensure greater results for them in the future. To achieve that, their soft skills need to be improved by using the PBL approach. This approach is relevant to the concept of 21st century learning, especially in education.